Creative Cultural Tourism for Health by Communities, Koh Kha District, Lampang Province - Intakhan, Phaithun; Pratuangboriboon, Nathdanai; Khamsan, Wanchai; Limpaiboon , Jaruwan; Bunvut, Saratchanut; Suwannaraj , Sonthiya; Srichanapun, Punchaporn; Sattaratanakhachon , Ketsanees; Tumtong, Thawatchai; Siriyod, Thagoon; Tawan, Kamonwan; Pankham, Chutinist; et al. (Area Based Development Research Journal, 2023)
Ko Kha District, Lampang Province has many interesting tourist attractions but has not yet been able to develop into a concrete cultural and creative tourist attraction for health because to date no systematic survey and assessment of its tourism potential has been implemented. The community lacks a tourist route that combines tourist attractions with creative activities and requires cost information to determine pricing schemes. The current research evaluates the potential of creative cultural attractions for health and establishes guidelines for the development of creative cultural tourism for community-based health. Key informants consist of community leaders, community philosophers, and tourism stakeholders in Ko Kha District. The processes include the following steps: 1) data collection of community-based creative cultural tourism destinations by the community, 2) assessment of the potential of community-based creative cultural tourism destinations by the community, 3) organization of creative cultural tourism destinations for health by the community, and 4) participatory program cost analysis in which the community funds are pooled for organizing creative activities for health. The use of community resources as part of co-inventing creative activities results in a creative cultural tourism route for health that promotes a healthy body, healthy mind, and community awareness of the tourism activity's costs thus they can determine appropriate prices. The tourist route test revealed tourists’ satisfaction with the program at a high level. They were most impressed by the following activities: in-depth knowledge of arts and culture provision through legend storytelling, horse carriage riding and horse feeding, and healthy mineral water spicy salad preparation. The issue of concern is the season to offer the program. In conclusion, the proposed itinerary best suits winter, but may need adjustment during the rainy season or summer to operate the program all year round.